2018
DOI: 10.1371/journal.pone.0199502
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the HIV Blot 2.2, INNO-LIA HIV I/II Score, and Geenius HIV 1/2 Confirmatory Assay for use in HIV confirmation

Abstract: In view of recent revised recommendations for human immunodeficiency virus (HIV) confirmatory testing, the performance of 3 HIV confirmatory assays was compared. Using the HIV Blot 2.2 (MP-WB), the INNO-LIA HIV I/II Score (INNO), and the Geenius HIV 1/2 Confirmatory Assay (Geenius), we tested 199 HIV-1 positive, 161 HIV negative, 65 HIV western blot indeterminate, 26 HIV seroconversion, 34 early HIV infection and 4 HIV-2 positive archived specimens. We show that all 3 assays had comparable test sensitivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…On the opposite, assays designed only to identify HIV-2 infection, HIV-2 Blot 1.2 and New Lav Blot II, exhibited high rates of undetermined results and misclassified as HIV-2 some HIV-1 only infections (7% and 5%, respectively), a consequence of cross-reactivity between HIV-1 antibodies and HIV-2 proteins. These results are consistent with previous studies regarding HIV-1 infection sensitivities and undetermined results for INNO-LIA (27,36,37), HIV Blot 2.2 (36,38), New Lav Blot I and II (39,40) and Geenius (27, 36-39, 41, 42), summarized in Fig. 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the opposite, assays designed only to identify HIV-2 infection, HIV-2 Blot 1.2 and New Lav Blot II, exhibited high rates of undetermined results and misclassified as HIV-2 some HIV-1 only infections (7% and 5%, respectively), a consequence of cross-reactivity between HIV-1 antibodies and HIV-2 proteins. These results are consistent with previous studies regarding HIV-1 infection sensitivities and undetermined results for INNO-LIA (27,36,37), HIV Blot 2.2 (36,38), New Lav Blot I and II (39,40) and Geenius (27, 36-39, 41, 42), summarized in Fig. 1.…”
Section: Discussionsupporting
confidence: 93%
“…New Lav Blot II and HIV-2 Blot 1.2 had reported sensitivities of at least 95% (32,43). INNO-LIA had a reported sensitivity of 100% (36,37), while sensitivity ranged from 85% to 100% for Geenius (27,(39)(40)(41)(42)44). However, most of these studies included a very limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Positive confirmation continues to be even more important as we expand initiation on antiretroviral therapy (ART) immediately after receiving HIV-positive test results [4]. The false positive rate observed by a testing algorithm can be significantly reduced by including a third HIV RT or by including a confirmatory test such as Geenius HIV-1/2 RT (Geenius) or HIV-1 Western blot (WB) [5][6][7][8]. However, the Geenius and WB tests are more complex, expensive, and require appropriate laboratory infrastructure and instrument maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Montesinos et al reported that five of 11 specimens from the acute phase of HIV-1 infection were identified as HIV-1-positive using Geenius [ 10 ]. Abbate et al [ 11 ] and Wong et al [ 12 ] reported that the sensitivity of the test for acute HIV-1 infection was low. Kondo et al reported that seven of 20 specimens from the acute phase of HIV-1 infection were identified as HIV-1-positive [ 13 ].…”
Section: Discussionmentioning
confidence: 99%